Representation of cultures and communities in a global ELT textbook: A diachronic content analysis - Keles, Ufuk; Yazan, Bedrettin (Language teaching research : LTR, 2023)
This study examines the representation of cultures and communities in the world across five editions of New Headway elementary level textbook (NHE). It conducts a diachronic content analysis to explore how the representation of cultures and communities has evolved in NHE across five editions since its first edition’s publication in 1993. Adapting Kachru’s model of concentric circles for data analysis, we utilized Yuen’s adaptation of ACTFL’s (1996) standards for language teaching via the categories of persons, perspectives, products, and practices. Our findings mainly indicate that the Inner Circle has maintained its dominance in NHE’s content over five editions. We found that there was an imbalance favoring European cultures against non-European cultures in the Expanding Circle. On the other hand, Expanding Circle / Non-European and Outer Circle are underrepresented with around 10% of the textbook content. These findings show that NHE’s cultural focus is on the Western, European, and Anglo-American world of English-speaking communities. Such an imbalance in representation of world cultures leads us to conclude that NHE’s writers do not sufficiently raise English learners’ global cultural consciousness since there has been little engagement with multicultural view of English language varieties. We invite teachers, learners, and material developers to critically approach, analyse, revise, and/or adapt textbook content as discursive constructions which shape the imagination of cultures and communities.